2021
DOI: 10.2478/aut-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

A Fabric-Based Integrated Sensor Glove System Recognizing Hand Gesture

Abstract: The research on wearable glove sensor system has been increasing over recent years because of the need for portability and comfort. This study presents a fabric-based integrated sensor glove system with five sensing zones. Five sensors are knitted by silver-plated nylon yarn and embedded into glove directly using intarsia technology. Various parameters including sensor elasticity, sizes of embedded sensor as well as glove are discussed, respectively. Further, selected or chosen integrated sensor glove is manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…Different hand motions were also detected by the knitted sensor developed by Han et al, but the electrical resistance change was not high enough to monitor the overall movements of the fingers [1]. Another study also studied the performance of the sensor in gloves for recognizing gestures and concluded that elasticity of the fabric affects the effective detection range of knitted sensors, the size of the sensor has a significant influence on sensitivity, and appropriate glove size helps to avoid non-linear sensing phenomenon [17]. Lee et al also concluded that the developed glove might be useful to amputees as a tool that allows them to rehabilitate or regulate the myoelectric prosthesis by putting the sensing elements into the glove and producing the whole garment knitting technique for ease of commercialization [18].…”
Section: Introductionmentioning
confidence: 99%
“…Different hand motions were also detected by the knitted sensor developed by Han et al, but the electrical resistance change was not high enough to monitor the overall movements of the fingers [1]. Another study also studied the performance of the sensor in gloves for recognizing gestures and concluded that elasticity of the fabric affects the effective detection range of knitted sensors, the size of the sensor has a significant influence on sensitivity, and appropriate glove size helps to avoid non-linear sensing phenomenon [17]. Lee et al also concluded that the developed glove might be useful to amputees as a tool that allows them to rehabilitate or regulate the myoelectric prosthesis by putting the sensing elements into the glove and producing the whole garment knitting technique for ease of commercialization [18].…”
Section: Introductionmentioning
confidence: 99%